MENILIK MAKNA KEHIDUPAN ISLAMI PADA SAJAK GURINDAM DUA BELAS BESERTA MAJAS YANG TERKANDUNG: STUDI SASTRA KLASIK - Alkhaerani, Siti (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2023)
Abstract One of the famous classical literary works of the Nusantara is the Gurindam Dua Belas. The Gurindam Dua Belas is a long poem consisting of 12 (twelve) chapters. This poem was created by Raja Ali Haji, a renowned writer in the 19th century, and therefore, Gurindam Dua Belas is written in the Malay language. Gurindam Dua Belas contains numerous pieces of Islamic advice aimed at humans, incorporating elements of Malay culture. This article describes a study on Islamic values contained in the poem. The study uses a contain analysis method. Conclusions were formulated based on the study. Firstly, the work employs various figures of speech such as metaphor, simile, personification, antithesis, periphrasis, symbolism, and hyperbole to embellish its verses. Secondly, the Islamic values conveyed in Gurindam Dua Belas are the importance of being a faithful believer in Allah, prioritizing matters of the hereafter over worldly affairs, being a person who shows devotion to family and friends, seeking a good environment, and being a humble leader. With the many Islamic values contained in it, this poem can be an example of a literary work that can be taught in madrasas or schools to develop good character while remaining literary. Abstrak Salah satu karya sastra klasik Nusantara yang terkenal adalah Gurindam Dua Belas. Puisi Gurindam Dua Belas adalah puisi panjang yang memiliki 12 (dua belas) pasal. Puisi ini dibuat oleh Raja Ali Haji, seorang sastrawan yang terkenal di abad ke-19, oleh karena itu, Gurindam Dua Belas menggunakan Bahasa Melayu. Gurindam Dua Belas banyak mengandung nasihat islami yang ditujukan kepada manusia dengan adanya percampuran Budaya Melayu di dalamnya. Artikel ini memaparkan hasil kajian terhadap nilai-nilai islami pada Gurindam Dua Belas karya Ali Haji. Kajian ini menggunakan analisis konten. Kesimpulan dirumuskan berdasarkan pada kajian ini. Pertama, Gurindam Dua B elas mengandung berbagai majas untuk memperindah tulisannya seperti metafora, simile, personafikasi, antitesis, perfrasis, simbolik, dan hiperbola. Kedua, nilai ajaran islami yang disampaikan pada Gurindam Dua Belas antara lain yaitu jadilah manusia yang beriman kepada Allah, pentingkanlah urusan akhirat dari pada dunia, jadilah manusia yang berbakti kepada keluarga dan teman, carilah lingkungan yang baik, serta jadilah pemimpin yang rendah hati. Dengan banyaknya nilai islami yang terkandung, sajak ini mampu menjadi contoh karya sastra yang dapat diajarkan di madrasah atau sekolah untuk menumbuhkan karakter baik dengan tetap bersastra.